Knowledge of the principles of healthy nutrition among women residents of Rzeszow administrative district - Sabina Lizis (University of Applied Sciences in Tarnow, Poland, 2019)
Aim of the study: Assessment of knowledge of the principles of healthy nutrition among women from the Rzeszow administrative district, taking into account their level of education. Material and methods: The study involving the method of diagnostic survey covered 300 women aged 30-40 years, residents of Rzeszow administrative district. The percentage shares of respondents' answers to individual survey questions were calculated. The collected research results were analyzed with the use of Chi-square (χ2). Results: Respondents largely correctly answered most of the questions in the survey. The answers to the question about the proportion of vegetable consumption in relation to fruit varied widely. The Chi-square test showed statistically significant differences in the frequency of obtaining information from training (p = 0.012) and specialist literature/magazines (p = 0.046). Conclusions: Knowledge of the principles of healthy nutrition among women from the Rzeszow administrative district is sufficient, although the respondents have a problem with determining the proportion of vegetable consumption in relation to fruit. Mostly women get knowledge about proper nutrition from a doctor and the Internet. The frequency of obtaining information from training and science piblications depends on the level of education. These sources are most often used by women with higher education, and least often by people with basic education.